KONSEPSI NILAI NILAI PENDIDIKAN HUMANIS-RELIGIUS MENURUT PAKOE BOEWONO IV (1788-1820) DALAM SERAT WULANG-REH - Sabar Narimo (Universitas Muhammadiyah Surakarta, 2014)
Pakoe Boewana IV is the King having many literary works, one of them is theWulang-Reh letters as the result of reflection, phylosophy, view of live, and his ambitionin contextualizing to the reality of life for the periode of 1788-1820. The Wulang-Rehletters consists of Kawruh Piwulang (sugesstion) or Pitutur Luhur (direction) teaching,reflected in the form of Pituduh lan Wewaler (instructions and prohibitions) having fullof humanic-religious life values. The values conception found in the Wulang-Rehlettersare (1) morality messages/ethics, (2) education value, (3) phylosophy value, and (4) religionvalue. The teachings above are relevant to be learned, to be implemented, becoming thebehavior and Indonesian nation nationality in the context of at present time.Kata Kunci: humanic value; religious; and the Wulang-Reh letters.Pakoe Boewana IV adalah raja dan pujangga yang memiliki banyak karyasastra, salah satunya adalah Serat Wulang-Reh, yang merupakan hasil refleksi,perenungan, falsafah, dan pandangan hidup, serta cita-citanya dalam membaca realitaskehidupan pada masa 1788-1820 M. Serat Wulang-Reh berisi ajaran tentang kawruhpiwulang atau pitutur luhur (tuntunan dan nasihat), yang berupa pituduh lan wewaler(perintah dan larangan), yang sarat dengan nilai-nilai kehidupan yang humanisreligius.Konsepsi nilai-nilai yang terkandung di dalamnya berupa (1) pesan moral/etika; (2) nilai pendidikan; (3) nilai filosofis; (4) nilai nilai religius. Ajaran-ajaran tersebutmasih relevan dipelajari, diamalkan, menjadi perilaku, dan kepribadian bangsa Indonesiadalam konteks kekinian.Kata Kunci: nilai humanis; religious; wulang reh.